PERAN TINGKAT PENDIDIKAN MEMODERASI CITRA MEREK DENGAN PREFERENSI MEREK LAMPU PHILIPS LED DI KOTA DENPASAR - Widyantari, Ni Kadek Sri; Suparna, Gede (E-Jurnal Manajemen, 2016)
The purpose of this study is  explain the effect of brand image and education level on brand preference, and explain the  role of  education level in moderating the influence brand image on the brand preference Philips LED lighting products . The sample was determined by using a non-probability sampling techniques, particularly purposive sampling. The sample size of 100 respondents to the survey method using a questionnaire measured with Likert scale, using analytical techniques Multiple Linear Regression and MRA (Moderated Regression Analysis). Simultaneously three variables (brand image, level of education, and interaction with the brand image of education level) significant and positive impact on brand preference Philips LED lighting products. Partially, the results showed that the brand image of the significant and positive impact on brand preference, while the level of education does not significantly influence brand preference. The level of education does not moderate the relationship between brand image with brand preference.
Keywords: education level, brand image, brand preference